Model Pembelajaran Kooperatif Untuk Meningkatkan Motivasi Belajar Siswa MTsN Sumber Bungur Pamekasan - ST Fatimah; Indari; Dalilah (MAN Insan Cendekia Jambi, 2024)
This article discusses cooperative learning models to increase student learning motivation. One of the factors that influence student motivation is teachers 30%, internal factors 23.4%, learning facilities 41.4%, environment 0.032%, intelligence 12.7% talent 43%, interest in learning 74.76%, motivation 0.379%, emotional 49.3%. Therefore, the Jigsaw Learning model is used to increase student learning motivation at MTsN Sumber Bungur Pamekasan. The method used descriptive qualitative Classroom Action Research (PTK) on 40 students, 21 students and 19 female students each, accompanied by a team of 29 expert teachers. The results of Jigsaw Learning using PTK show that cycle I produces learning motivation of 69.31%. Meanwhile, student learning in cycle II experienced an increase of 70.4%. The application of Jigsaw Learning can significantly increase learning motivation in cycle II with an average student score of ≥ 68.